Acute upper gastrointestinal bleeding - Kurien, Matthew (Clin Med (Lond), 2015)
Acute upper gastrointestinal bleeding (AUGIB) is a frequently encountered medical emergency with an incidence of 84–160/100000 and associated with mortality of approximately 10%. Guidelines from the National Institute for Care and Care Excellence outline key features in the management of AUGIB. Patients require prompt resuscitation and risk assessment using validated tools. Upper gastrointestinal endoscopy provides accurate diagnosis, aids in estimating prognosis and allows therapeutic intervention. Endoscopy should be undertaken immediately after resuscitation in unstable patients and within 24 hours in all other patients. Interventional radiology may be required for bleeding unresponsive to endoscopic intervention. Drug therapy depends on the cause of bleeding. Intravenous proton pump inhibitors should be used in patients with high-risk ulcers. Terlipressin and broad-spectrum antibiotics should be used following variceal haemorrhage. Hospitals admitting patients with AUGIB need to provide well organised services and ensure access to relevant services for all patients, and particularly to out of hours endoscopy.